Citra Perempuan dalam Novel Laut Bercerita karya Leila S. Chudori: Image of Women in Sea Story Novel by Leila S. Chudori - Mardiana, Elke Aulia Putri; Apriyani, Tristanti (Balai Bahasa Provinsi Papua, 2023)
This study aims to describe the dominant image of women depicted in the novel Laut Bercerita by Leila S Chudori. The problem that arises in this study is how is the image of a female character named Asmara Jati in the novel Laut Bercerita by Leila S Chudori. This research includes the type of qualitative descriptive research. The data were taken from reading the novel Laut Bercerita by Leila S Chudori in the form of words and direct and indirect sentences. Data collection techniques in this study were carried out using the read-and-note method. The data is then identified and analyzed based on the theory of feminist literary criticism from Ruthven's perspective. In this article, the image of female characters is found, including self-image and social image. Women's self-image consists of physical and psychological images. In the physical image, Asmara Jati is described as a young, assertive woman. In the psychic image of Asmara Jati, it is described as a woman with a stable psyche, tough, intelligent, brave, compassionate, and caring. Meanwhile, the social image consists of the family and society. The image in the family of Asrama Jati figures as a child, a younger sibling, and a family member with a high sense of caring and love for their parents. Meanwhile, the image in the Asmara Jati community is that of a woman who is active, caring, responsible, and a driving force for the Commission on Missing Persons.